2020
DOI: 10.17505/jpor.2020.22404
|View full text |Cite
|
Sign up to set email alerts
|

“Doing” mindsets in the classroom: A coding scheme for teacher and student mindset-related verbalizations

Abstract: There is a growing body of research showing the crucial role that students’ growth versus fixed ability-mindsets have in their school achievement, enjoyment, and resilience. The overwhelming majority of this research adopts a variable-oriented approach. As a result, little is known about how teachers and students co-regulate each other’s mindsets within classroom interactions. This manuscript addresses the need for more person-oriented research that examines how teachers and students do mindsets in naturalisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…As the difficulty of courses in college is higher than that in high school, the fixed mindsets of undergraduates may be higher than that of high school students. Moreover, the fixed mindsets of teachers also influence the mindsets of students (de Ruiter et al, 2020;Davison et al, 2021). Scherr et al (2017) paid attention to the fixed mindsets in physics graduate admissions and found that many teachers would choose students with a talent in physics so that they can be competent for more difficult graduate courses.…”
Section: Introductionmentioning
confidence: 99%
“…As the difficulty of courses in college is higher than that in high school, the fixed mindsets of undergraduates may be higher than that of high school students. Moreover, the fixed mindsets of teachers also influence the mindsets of students (de Ruiter et al, 2020;Davison et al, 2021). Scherr et al (2017) paid attention to the fixed mindsets in physics graduate admissions and found that many teachers would choose students with a talent in physics so that they can be competent for more difficult graduate courses.…”
Section: Introductionmentioning
confidence: 99%
“…A promising method for the observation of real life situational attributions and responses is behavioral coding. De Kraker-Pauw et al (2017) and De Ruiter et al (2020), for example, use coding schemes to organize categories of observable verbalizations and behavior that are performance versus learning-oriented. Quantitative analytical methods, such as timeseries analysis, can then be used to analyze how mindset relevant behaviors are organized temporally during social interaction.…”
Section: Research Agendamentioning
confidence: 99%
“…Quantitative analytical methods, such as timeseries analysis, can then be used to analyze how mindset relevant behaviors are organized temporally during social interaction. De Ruiter et al (2020), for example, demonstrated that the moment to moment variability that teachers and students demonstrate (i.e., variability between learning and performance-behavior) can be synchronized across their interaction. Qualitative analytical methods, such as conversation analysis, could elucidate how students’ learning orientation is directed in social interactions, and how mindset information (e.g., feedback) is conveyed and understood (see Gardner, 2008; Koole, 2012).…”
Section: Research Agendamentioning
confidence: 99%